The Boundaries in Boris Senker’s Istarska prikazanja - Ljubić, Lucija (Poznańskie Studia Slawistyczne, 2025)
Senker’s most recent dramatic trilogy, Istarska prikazanja (2023) includes the mystery play Istarska priča, the miracle play Sanjari budućnosti and the morality play Sanjarova priča. Istarske priče premiered in 2018 and Sanjari budućnosti in 2019, both in the Fort Forno Theatre in Bale, while Sanjarova priča premiered in 2023 in the Požega City Theatre, in co-production with the Osijek Academy of Arts and Culture. Istarska prikazanja go beyond the boundaries of three medieval theatre genres, transcending geographical boundaries and commitment to only one language or homeland. Situating the trilogy in the playwright’s so called “native” cycle, the paper examines the strategies the playwright uses to invent the homeland and its history while he parallelly portrays, erases and crosses its borders regarding theatre and literary history.